Metadrama: Rewritings and Forgeries in Shakespeare, Barrales and Radrigán (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The following article approaches two rewritings of William Shakespeare’s work within current Chilean playwriting: Shakespeare falsificado: reconstrucción falsificada de un manuscrito censurado (2011), by Luis Barrales and La Tempestad (2015), by Juan Radrigán. It proposes rewriting as a metadramatic exercise, a conscious gesture -both political and dramatic- that seeks to establish dialogue and discussion with its original, inscribing a new authorial perspective within the cultural tradition continuum. With this approach, this work exposes, first, characteristics from English renaissance dramaturgy as a hybrid praxis, collaborative, refounding and political. Then, it characterises both rewritings as practice that showcase the currency and continuation of a cultural, literary and dramatic canon through different articulations that print themselves in our voices. Likewise, Barrales and Radrigan’s perspectives display themselves as political gestures expressed towards their contexts.
Keywords: William Shakespeare; Luis Barrales; Juan Radrigán; metadrama; rewriting; political theatre.